Pengaruh Pembiayaan Syariah terhadap Profitabilitas: Moderasi Pembiayaan Bermasalah pada Bank Umum Syariah di Indonesia - Musviyanti; Syahrani (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the impact of profit-sharing, purchase resale, and leasing (ijarah) on profitability, with non-performing financing (NPF) as a moderating variable, in Sharia commercial banks in Indonesia from 2017 to 2020. The research sample consists of panel data from nine Sharia banks registered with the Financial Services Authority (OJK) during the specified period. The performance of Sharia banks is measured using return on assets (ROA). The findings indicate that profit-sharing has a positive but not statistically significant effect on profitability (ROA). In contrast, purchase resale has a positive and significant effect on profitability (ROA), while leasing (ijarah) also shows a positive but non-significant effect on profitability (ROA). The results of the moderated regression analysis (MRA) reveal that the NPF variable moderates the relationship between purchase resale and profitability (ROA). However, NPF does not moderate the effects of profit-sharing or leasing (ijarah) on profitability (ROA).